2016
DOI: 10.1590/0074-02760160134
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal efficacies of plants from Midwestern Brazil: melianodiol from Guarea kunthiana as a potential biopesticide against Aedes aegypti

Abstract: A total of 36 ethanol extracts from different anatomical parts of 27 plant species (18 families), native to the Pantanal and Cerrado biomes in Midwest Brazil, was assessed for their effect against Aedes aegypti larvae, the vector of dengue, hemorrhagic dengue, Zika and chikungunya fevers. Only the extract obtained from seeds of Guarea kunthiana (Meliaceae) proved active (LC50 = 169.93 μg/mL). A bioassay-guided investigation of this extract led to the isolation and identification of melianodiol, a protolimonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…A triagem preliminar é considerada uma boa abordagem para a avaliar o potencial larvicida dos compostos e extratos (AMER; MEHLHORN, 2006;MC;SAJITH;CC, 2015;SARMENTO et al, 2016). Essa abordagem, a 2000 mg/L, foi empregada neste estudo para determinar as propriedades larvicidas dos extratos hidroalcoólicos das seis espécies listadas na Tabela 1.…”
Section: Resultsunclassified
“…A triagem preliminar é considerada uma boa abordagem para a avaliar o potencial larvicida dos compostos e extratos (AMER; MEHLHORN, 2006;MC;SAJITH;CC, 2015;SARMENTO et al, 2016). Essa abordagem, a 2000 mg/L, foi empregada neste estudo para determinar as propriedades larvicidas dos extratos hidroalcoólicos das seis espécies listadas na Tabela 1.…”
Section: Resultsunclassified
“…The result revealed that this natural product could be a potential candidate for the development of new biocontrol agents against Ae. aegypti larvae [71].…”
Section: Natural Products From Brazilian Biodiversity As a Source Of mentioning
confidence: 99%